Qualidade de sementes de girassol em função da posição no capítulo e da densidade de plantas - Oliveira, Carlos Manoel de (2013)
The increasing demand for sunflower seed aiming at making edible oil and biofuel is reflected on the seed market since the requirement for quality seeds has become bigger and bigger in recent years. This work aimed to evaluate the quality of sunflower seeds according to the position their in the chapter, to the seedling density, and to the seed weight by means of an experiment at the seed research laboratory of Universidade Federal de Uberlândia s Instituto de Ciências Agrárias. The experimental design followed randomized blocks with five replications in a split plot. The evaluation focused on seedling density in the plot, seed position in the chapter in the subplot, and seed weight in the subsubplot. Characteristics evaluated encompasses the proportion of fractions (heavy and light), a thousand seed mass, normal and abnormal seedlings percentage as well as dead seed percentage through germination test, emergence percentage, emergence speed rate, starting time, ending time and average time, coefficient of time variation, sync, uncertainty and relative frequency of emergence. These data came from the emergence test in sand. It was concluded that seedling density up to 40 thousand seeds per hectare allows to obtain greater-mass seeds; seeds considered to be heavy pose better plants emergence; higher rates of emergence speed are obtained when seeds come from the central position in the chapter, as it does both shorter final and medium emergence terms and lower coefficient of variation in time; the emergence of seeds in the central position of the chapter was more synchronized than of those seeds emerged in its periphery. The evaluation of sunflower plants in sand rows is important, above all, to obtain relevant results concerning the position of seeds in the chapter.